Efektivitas Penerapan Disinfektan Alami Campuran Serbuk Kulit Nanas dan Arang Aktif dalam Menurunkan Jumlah Bakteri Coliform Pada Air Bersih - Shinta Nur Atikah; Narto Narto; Lilik Hendrarini (Sanitasi: Jurnal Kesehatan Lingkungan, 2016)
Coliform bacteria is an indicator of fecal water contamination. The number of coliform bacteria in water can cause illness in humans who consume the water. One of the efforts to decrease it is by using disinfectants. The purpose of this study was to determine the effectiveness of natu-ral disinfectant made from the mixture of pine-apple peels powder and activated charcoal for decreasing MPN Coliform in water. The study was a pre-experiment with one group pre-test post-test design. There were three variation of the disinfectants, i.e. 1:1, 1:2 and 1:3 ratios, in two exposure times, and each was applied to 5 liters of coliform contaminated water, in three replications. The examination of water were conducted in Microbiology Laboratory of Environ-mental Health Department of Yogyakarta Polytechnic of Health. The result of statistical analysis by using paired t-test at ? 0,05 obtained a p value of 0,003; which means that the pre-test and post-test of the MPN Coliform were significantly different. The subsequent results by one way anova test at same ?, for 30 minutes exposure the obtained p-value was 0,249; and for 60 minutes exposure the p-value was 0,724. It means that the post-test examination of MPN Coli-form among the doses and time variations were not signifcantly different. Based on the results it can be concluded that the mixture of pineapple peels powder and activated charcoal as natural disinfectant affects the decrease pf MPN Coliform in water. However, the reduction differences among the three doses and the two exposure times under study were not significant.